Integrating Nationalist Character and Social Care Education in Islamic Elementary Schools - Abdussalam DZ; Imam Tabroni; Bambang Firmansyah; Maftuhah Dewi; Muhamad Parhan; Eti Nurhayati; Heramb Kulkarni (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Character education is a central concern in Islamic elementary schools as they are expected to cultivate students’ religious values alongside nationalist attitudes and social responsibility in an increasingly complex social context. This study aims to examine the implementation of nationalist character education and social care education, including the strategies employed, challenges encountered, and outcomes achieved in an Islamic Elementary School. The research employed a qualitative descriptive method with a case study design and collected data through in-depth interviews and document analysis. The findings indicate that nationalist character education has been systematically integrated into school culture through routine activities such as flag ceremonies, morning assemblies, and the practice of national songs, thereby effectively fostering students’ sense of national identity. In contrast, social care education is implemented mainly through community-based programs, including charitable activities such as distributing rice packages to underprivileged communities. However, the study also reveals persistent challenges in strengthening students’ social sensitivity, particularly regarding environmental cleanliness and empathy toward others. These results highlight an imbalance between the development of nationalist values and social care behaviors. This research implies that Islamic educational institutions need more holistic and consistent strategies to integrate nationalist character education and social care within Islamic education curricula to enhance students’ moral, civic, and social responsibility.